PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA JASA PENGIRIMAN SHOPEE XPRESS KEBAGUSAN RAYA PASAR MINGGU - Septyana, Elsa; Khoirul, Umam; Grade Tampubolon, Endy (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
This study aims to determine the effect of service quality on customer satisfaction at Shopee Xpress Kebagusan Raya Pasar Minggu delivery service. The research method used in this study is a descriptive approach quantitative method to determine how much influence the independent variable (service quality) has on the dependent variable (customer satisfaction). The analysis technique used, namely simple linear regression analysis technique, correlation coefficient, coefficient of determination, and t test with the help of Microsoft Excel and manually. Based on the results of the research, a simple linear regression calculation was obtained Y = -3.293 + 0.368X. then in the t test the results showed the t_count value of the service quality variable of 9.6765> t_table 1.660. This shows that the quality of service at Shopee Xpress Kebagusan Raya Pasar Minggu delivery service has a significant effect as a determinant of customer satisfaction at Shopee Xpress Kebagusan Raya Pasar Minggu delivery service.